THE EFFECT FOUR SQUARE STRATEGYTOWARD STUDENTS VOCABULARY MASTERY AT SEVENTH GRADE IN SMPN 02 KOTO BARU DHARMASRAYA - Salsa Arsidilla; Elsi Amiza (STKIP Subang, 2026)
This research the reseacher found that Some of the problems were: students find itdifficult to memorize new vocabulary,the students preferred to use indonesian language duringthe teahing and leraning process than English in general the students had difficult to understandlearning English. This research used a quasi-experiment using non-equivalent control groupdesign. The samples used were class VII D as experimental class consisted of 33 students andVII E as control class consisted of 33 students. The results of this research for the first hypothesisusing a paired sample t-Test, it was found that Sig (2-tailed) < 0.05, so the hypothesis alternative(Ha) was accepted, indicating that there is a significant effect of using the four square strategy.Next, for the second hypothesis using a independent sample t-Test, it was found that Sig (2-tailed) < 0.05, so the hypothesis alternative (Ha) was accepted, indicating that there is asignificant difference between the class that used four square strategy and the class that do notused four square strategy. And for the third hypothesis using a independent sample t-Test, it wasfound that Sig (2-tailed) < 0.05, so the hypothesis alternative (Ha) was accepted, indicating thatthe vocabulary mastery of students who use the four square strategy was better than that studentswho do not used four square strategy. So, it can be concluded that the four square strategy had aeffect on students vocabulay mastery.